ANALISIS PENERAPAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN IPA SISWA KELAS VIII SMP NEGERI KOTA PEKANBARU - Rahmawati, Sari; Arnentis, Arnentis; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research has been conducted at Pekanbaru City Junior High School in October to November 2018 which aims to determine the implementation of the scientific approach to science learning in class VIII students of Pekanbaru City Junior High School using purposive sampling technique. The samples used in this study were grade VIII teachers, totaling 10 teachers, namely SMPN 1 Pekanbaru, SMPN 3 Pekanbaru, SMPN 4 Pekanbaru, SMPN 6 Pekanbaru, SMPN 7 Pekanbaru, SMPN 10 Pekanbaru, SMPN 12 Pekanbaru, SMP N 14 Pekanbaru, SMPN 20 Pekanbaru and SMPN 23 Pekanbaru. The instruments used were scientific approach questionnaire, observation sheet and document assessment sheet. Furthermore, the data were analyzed by the value of the product moment at the level of 5% using the SPSS application and descriptive analysis was carried out. The results of the questionnaire validation scientific approach in stage I with a significant level of 5% with 5 respondents, which is equal to 0.878 and found that the questionnaire is not yet valid. Then stage II validation was carried out with a significance level of 5% with 10 respondents, which was equal to 0.632 with the results of 4.50 with very good criteria. Based on the results of the study it can be concluded that what is done in the implementation of the scientific approach to science learning in eighth grade students of Pekanbaru City Middle School shows that the scientific approach has been implemented very well.Key Words: Analysis, scientific approach, science learning